Cardiac thrombosis in a patient with Behcet's disease: Two years follow-up - (:unkn) unknown (KLUWER ACADEMIC PUBL, 2000)
A 28-year-old man with Behcet's disease was presented with cardiac symptoms in addition to previous complaints of oral and genital ulcers. A diagnosis of thrombosis was made and patient began to receive anticoagulant and immunosupressive therapy and was followed by echocardiographic examination. Despite medical therapy, thrombosis recurred. Surgical excision was performed and histological findings were consistent with organizing thrombus. Nature of cardiac involvement and review of literature on cardiac thrombosis in Behcet's disease was discussed.
Keywords: Behcet's disease; cardiac thrombosis; echocardiography; VALVE PROLAPSE; MANIFESTATIONS; INVOLVEMENT